2007
DOI: 10.1016/j.reprotox.2007.06.004
|View full text |Cite
|
Sign up to set email alerts
|

In vivo effects of bisphenol A in laboratory rodent studies

Abstract: Concern is mounting regarding the human health and environmental effects of bisphenol A (BPA), a high-production-volume chemical used in synthesis of plastics. We have reviewed the growing literature on effects of low doses of BPA, below 50 mg/kg/day, in laboratory exposures with mammalian model organisms. Many, but not all, effects of BPA are similar to effects seen in response to the model estrogens diethylstilbestrol and ethinylestradiol. For most effects, the potency of BPA is approximately 10 to 1,000-fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

25
733
0
8

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 1,029 publications
(783 citation statements)
references
References 204 publications
25
733
0
8
Order By: Relevance
“…Issues relating to BPA were extensively discussed by five panels of experts prior to and during the meeting, and are summarized in five reports included in this issue: (1) human exposure to bisphenol A (BPA) [1]; (2) in vitro molecular mechanisms of bisphenol A action [2]; (3) in vivo effects of bisphenol A in laboratory animals [3]; (4) an ecological assessment of bisphenol A: evidence from comparative biology [4]; (5) an evaluation of evidence for the carcinogenic activity of bisphenol A [5]. Further discussion occurred at the meeting where participants from the panels were reorganized into four breakout groups.…”
Section: Introductionmentioning
confidence: 99%
“…Issues relating to BPA were extensively discussed by five panels of experts prior to and during the meeting, and are summarized in five reports included in this issue: (1) human exposure to bisphenol A (BPA) [1]; (2) in vitro molecular mechanisms of bisphenol A action [2]; (3) in vivo effects of bisphenol A in laboratory animals [3]; (4) an ecological assessment of bisphenol A: evidence from comparative biology [4]; (5) an evaluation of evidence for the carcinogenic activity of bisphenol A [5]. Further discussion occurred at the meeting where participants from the panels were reorganized into four breakout groups.…”
Section: Introductionmentioning
confidence: 99%
“…BPA has also been shown to bind to a membrane-associated ER and produce non-genomic steroid actions (Wetherill et al 2007) with the same efficacy and potency as estradiol (Alonso-Magdalena et al 2005;Hugo et al 2008). Whatever the mechanism, BPA can cause effects in animal models at doses in the range of human exposures, indicating that it can act at lower doses than predicted from some in vitro and in vivo assays (Richter et al 2007;Vandenberg et al 2007;vom Saal et al 2007;Wetherill et al 2007). …”
mentioning
confidence: 99%
“…However, the RfD for BPA (50 µg/kg/day) was calculated using the lowest observable adverse effect level (LOAEL) and 1,000-fold safety factors because a NOAEL had not been determined (Welshons et al 2003). More than 150 published studies describe BPA effects in animals exposed to < 50 mg/kg/day, including altered development of the male and female reproductive tracts, organization of sexually dimorphic circuits in the hypothalamus, onset of estrus cyclicity and earlier puberty, altered body weight, altered organization of the mammary gland, and cancers of the mammary gland and prostate; > 40 of these studies examined doses less than the RfD (Richter et al 2007). Many of these end points are in areas of current concern for human epidemiological trends (Soto et al 2008;Vandenberg et al 2009).…”
mentioning
confidence: 99%
“…Experiments based on exposing animals to the BPA during gestation or early postnatal period showed that histopathological changes are induced in target organs that persist lifelong and dictates additional changes upon further exposures to toxic chemicals later on during the animal's life (Richter et al, 2007). BPA acts via ERα and ERβ or the membrane bound forms of ERα present in estrogen-target organs and may induce complex and varied phenotypes depending on which receptor is responding.…”
Section: Critical Periods Of Exposures To Edcsmentioning
confidence: 99%
“…BPA was also reported to increase the number of terminal end buds lateral branching and epithelial density, the presence of secretory products within the alveoli and increased stromal cell nuclear density (Markey et al, 2001;Munoz-de-Toro et al, 2005;Durando et al, 2007). Furthermore, BPA has been shown to cross the placenta in rodents and increase the bioavailability of estrogens at the fetal circulation (Richter et al, 2007).…”
Section: Bisphenol a (Bpa)mentioning
confidence: 99%